Sensitivity of wet blood smear examination, modified Knott’s method and Polymerase chain reaction for diagnosis of Dirofilaria immitis infestation in dogs, and its therapeutic management - Das, Manisha; Patra, Ramesh; Senapati, S K; Sahoo, Rajasri; Panda, Sonali; Sahoo, P K (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Despite the combination of favourable climate for parasite, vectors and large population of stray dogs, information concerning the epidemiology and management of canine vector borne diseases in India is limited. Accurate identification of filarial species can be clinically important because of zoonotic concern and therapeutic implications. The present study was carried out in different breeds of dogs to document accurate identification of dirofilarial species from cases presented to VCC, of the College of Veterinary Science and Animal Husbandry, Bhubaneswar and Odisha State Govt. Veterinary Hospital at Sahid nagar, Bhubaneswar. The selection dogs for screening was based on clinical signs, and screening was done using conventional methods such as wet flim and modified Knott’s method, and PCR. Sixty five suspected cases were screened out of which 38 were detected positive by conventional method and 42 from highly sensitive PCR method which revealed 4 suspected samples, negative on conventional method, positive on PCR assay. In the present investigation, 42  samples were positive for D.immitis, out of 65 samples from PCR which clearly revealed that through PCR the samples those were positive by conventional methods of screening were positive and 4 suspected samples that were detected as negative by onventional method was found to be positive.
Keywords: Dirofilaria immitis; Polymerase chain reaction; wet blood smear; modified knott’s method; diagnosis